Localisation des zones d'accès à l'eau en saison sèche par analyse multicritère dans le bassin versant du Goudébo (région de Yakouta, Burkina Faso) - Lucien Ouédraogo; Blaise Ouédraogo; Oumar Kaboré; Pawendkisgou Isidore Yanogo; Tanga Pierre Zoungrana; Ibrahim Bouzou Moussa (Physio-Géo)
The study aims to identify areas where agro-pastoralists access to water during the dry season in the drainage basin of the river Goudébo. The approach is the spatial reference analysis AMC-RS based on Geographic Information System and Multi-Criteria Analysis. Water points used for different needs (boulis, drillings, ponds, tanks, sumps, wells and dams) were identified with the people. Cartographic documents and field surveys have constitute, through the GIS, a map database of these elements. Taking into account the travel times allowed a spatial representation of the accessibility to water points. The AMC-RS were made from the results of GIS, on the basis of criteria proposed by the people during the interviewing sessions. The results of the analysis gave 7.4 % of areas with a high level of aggregate access to different types of water point. These relatively small areas are circumscribed around 40 % of the villages. The importance taken by dams, and particularly that of Yakouta, puts the problem of the management of their feed area in the future.geographic information system, multi-criteria analysis, access to water, Burkina Faso